Nandrolone decanoate reduces the positive effects of resistance training on cognition, anxious behavior, and hippocampal morphology in rats (Research, Society and Development, 2022)
AAs became popular among competitive athletes and the general population for recreational and performance purposes. The indiscriminate use of AAs occurs in supraphysiological doses and negatively affects cognition.   Moreover, nandrolone decanoate (DECA) abuse may reduce the beneficial effects of resistance training (RT) on health. Objective: We aimed to investigate if DECA administration in supraphysiological doses interferes with the positive effects of RT on anxious behavior, memory, and morphology of neurons in the hippocampus of rats. Materials and Methods: Rats were randomly assigned into four groups (N= 12): Control (C); DECA (D); Trained (T) Trained+DECA (TD). EAA DECA was administered in daily supraphysiological doses of 15mg/kg during the 8 weeks of the RT protocol. All groups performed a maximum load test before and after the RT protocol; anxious behavior and memory tests were performed, and thereafter, rats were euthanized for morphologic analyses of the hippocampus.  DECA produced an anxiogenic effect, worsened cognition and reduced the thickness of the grainy layer of the DG in the hippocampus. Moreover, DECA reduced the positive effects of RT on cognition and DG neurons. This is the first study showing that suprapharmacological doses of DECA reduce the positive effects of RT on memory and the thickness of the granular layer of the DG.